Molecular characterization of a glycerol-3-phosphate acyltransferase reveals key features essential for triacylglycerol production in Phaeodactylum tricornutum. Issue 1 (December 2016) - Niu, Ying-Fang; Wang, Xiang; Hu, Dong-Xiong; Balamurugan, Srinivasan; Li, Da-Wei; Yang, Wei-Dong; Liu, Jie-Sheng; Li, Hong-Ye
Abstract Background The marine diatom, Phaeodactylum tricornutum, has become a model for studying lipid metabolism and its triacylglycerol (TAG) synthesis pathway makes it an ideal target for metabolic engineering to improve lipid productivity. However, the genetic background and metabolic networks of fatty acid biosynthesis in diatoms are not well understood. Glycerol-3-phosphate acyltransferase (GPAT) is the critical enzyme that catalyzes the first step of TAG formation. So far, characterization of GPAT in marine microalgae has not been reported, especially at the level of comprehensive sequence-structure and functional analysis. Results A GPAT was cloned fromP. tricornutum and overexpressed inP. tricornutum . Volumes of oil bodies were produced and the neutral lipid content was increased by twofold determined by Nile red fluorescence staining. Fatty acid composition was analyzed by GC–MS, which showed significantly higher proportion of unsaturated fatty acids compared to wild type. Conclusion These results suggested that the identified GPAT could upregulate TAG biosynthesis inP. tricornutum . Moreover, this study offers insight into the lipid metabolism of diatoms and supports the role of microalgal strains for biofuels production.